ECONOMIC ASSESSMENT OF THE EFFECTIVENESS AND SAFETY OF THE COMMONLY PRACTICED PERIOPERATIVE ANTIBIOTIC PROPHYLAXIS (BASED ON AN EARLIER EPIDEMIOLOGICAL SURVEY OF MULTIDISCIPLINARY HOSPITALS) - Yu. M. Gomon; A. S. Kolbin; S. V. Sidorenko; A. M. Kuzhel’; A. V. Repina; Yu. V. Lobzin; Yu. E. Balykina (Фармакоэкономика)
A survey conducted in four hospitals located in the city of St. Petersburg revealed that the commonly used perioperative antibiotic prophylaxis (PAP) did not follow (in 88% of cases) the guidelines approved for national clinical practice.Aim. To perform a cost-effectiveness analysis of the commonly practiced PAP among patients with clean, clean-contaminated and contaminated surgical wounds in a multidisciplinary hospital.Materials and methods. The PAP cost-effectiveness analysis was performed using the data from a multicenter epidemiological survey and previously conducted studies. The Markov model was used to compare the effectiveness and safety of the commonly used PAP with that recommended by the clinical practice guidelines. The rate of surgical site infection (SSI) and antibiotic-associated diarrhea (AAD) were chosen for the endpoints.Results. The costs associated with a single case of PAP according to the clinical practice guidelines was 3.5 times less than that associated with the PAP used in the common practice (RUB 4913,67 and 17837,71 respectively). The present analysis demonstrates that the PAP recommended by the clinical practice guidelines was more cost-effective as compared with the commonly practiced PAP.Conclusion. Regular epidemiological monitoring is required to improve effectiveness and safety of the existing PAP practice.